Diagnosis, treatment and supportive management of chronic lymphocytic leukemia: recommendations of the Dutch HOVON CLL working group. Issue 10 (24th August 2022) - Raa, Doreen G. Te; van der Straten, Lina; van Gelder, Michel; Kersting, Sabina; Levin, Mark-David; Mous, Rogier; van der Straaten, Hanneke M.; Nijziel, Marten R.; van der Spek, Ellen; Posthuma, Eduardus F. M; Visser, Hein P.J; van der Klift, Marjolein; et al.
Abstract: Management of patients with chronic lymphocytic leukemia (CLL) is changing due to considerable advances in the therapeutic armamentarium, and new therapies will possibly continue to emerge in the near future. Therefore, the CLL working group of the Dutch-Belgium Haemato-Oncology Cooperative Group for Adults in the Netherlands (HOVON) necessitated revising the Dutch CLL guidelines. The current guideline is based on the expert opinion of the HOVON CLL working group members and focusses on well-designed clinical trials taking into account efficacy with special emphasis on toxicity, treatment duration and treatment intensity. This article provides recommendations on diagnosis, treatment strategies in front-line and relapsed setting and provides supportive care measurements during novel-based therapies as well as for infectious CLL-related complications. The recommendations presented here are intended to provide guidance for the management of CLL patients in the Netherlands, and take into account the availability of treatment strategies at the time of this publication.